Coccygodynia combined with lumbosacral pain syndromes. A case series and clinical recommendations - Vadym V. Biloshitsky; Mychaylo V. Khyzhnyak; Yuriy E. Pedachenko; Oleksiy A. Eroshkin; Andriy M. Furman; Dmytro M. Romanukha (Ukrainian Neurosurgical Journal)
Coccygodynia (CD) is characterized by pain in the coccyx area, but in some cases the pain radiates to the sacrum, perineum, anus, genitals, gluteal area, sacroiliac joint, lower lumbar spine and thighs. The association of СD with other pain syndromes can lead to complicated diagnosis and non-targeted treatment, which will not improve the patient's condition. Objective: To investigate the frequency of the combination of low back pain in patients with CD who underwent spinal surgery and to evaluate the effectiveness of their treatment. Materials and methods: An analysis of the results of 62 interventions on Ganglion Impar (GI) in 54 patients was performed. Interventions were performed in the three medical centers in Kyiv, Ukraine in the period from 2017 to 2024: Main Medical Clinical Center of the Ministry of Internal Affairs of Ukraine, Romodanov Neurosurgery Institute and MedClinic Medical Center. Results. 14.8% of all study participants had post-traumatic CD (history of falling on the coccyx), in one case CD was caused by pelvic cancer, the vast majority of 83.3% had idiopathic CD. 21 (38.9%) of the study participants were male and 33 (61.1%) were female aged 23 to 84 years (mean age 48.0±15.4 years). In our series, 16 (29.6%) patients had lumbar or sciatic syndrome. Following treatment for CD, all patients noted a significant reduction of low back pain. In 4 (7.4%) observations, the intervention on GI was performed after lumbosacral spine stabilization surgery. Conclusions: Surgical treatment of spinal pathology in patients with СD partially reduced the intensity of the pain syndrome. The execution of the GI steroid block ensured the achievement of a stable analgesic effect during the six-month follow-up. Patients presenting with CD accompanied by lumbago or radiating pain require an integrated approach to ensure accurate differential diagnosis and optimal treatment outcomes.